Integrasi Integrasi Nilai Amanah dalam Kepemimpinan Islam: Sintesis Konseptual untuk Operasionalisasi Fungsi Manajemen Sumber Daya Insani - Muhammad Qasidy; Norvadewi (Jurnal Ilmiah Ekonomi Islam, 2026)
This study aims to analyze how the value of amanah (trustworthiness) can be operationalized within Islamic leadership practices in Human Resource Management (HRM). Unlike previous studies that tend to remain at the normative-theological level, this research offers a conceptual synthesis that translates amanah into measurable managerial indicators within HRM functions. A qualitative approach with a descriptive-analytical design was employed through a systematic library research method covering academic literature from 2022–2026. Data were analyzed using content analysis and thematic analysis to identify conceptual patterns and synthesize key ideas from the literature. The findings reveal that amanah is not merely a normative ethical principle, but can be translated into operational HRM indicators: in planning and recruitment, amanah is reflected through selection objectivity, process transparency, and the elimination of nepotism; while in development and performance evaluation, it is manifested through open performance information and equitable access to competency development. These findings suggest that integrating amanah values can strengthen organizational integrity and accountability, thereby serving as a foundation for designing more ethical and sustainable HRM leadership policies and governance.